The significance of employer branding in the consulting industry : An analysis of big 4 companies’ appeal to young talent in the Finnish context - Henriksson, Laura (My University, 2024)
The study researches the significance of employer branding when attracting and recruit ing young talents. To narrow the research the focus is on the attraction of working for the Big 4 companies The research looks at how the expectations about the company change with time and with work experience in the company. The possibility of change in perceptions offers a research gap to be covered in this thesis, as there is a shortage of research on how expectations and perceptions have changed after employment. The objective of this research is to discover the answers to the following research ques tions. 1. What elements of employer branding do young talents perceive as important when searching for employment in a potential company? The aim of the first question is to study the importance of employer branding on a more general level. In addition, the formatting of the research question gives the possibility to inspect the subject vastly. The second research question focuses more specifically on the employer branding of the Big 4 companies. 2. How important is an employer brand in attracting young talents to Big 4 com panies?

Työnantajamielikuva on tärkeää yrityksille heidän houkutellessa uusia työntekijöitä. Suurten konsultointiyhtiöiden, kuten Big 4 yritysten (EY, PwC, KPMG ja Deloitte) ei tar vitse tehdä itseään tunnetuksi, sillä heidän brändinsä on jo tunnettu konsultointialalla. Työnantajamielikuvan voi ajatella vaikuttavan näidenkin yrityksien potentiaalisiin uusiin työntekijöihin. Tässä tutkimuksessa tavoitteena on selvittää työnantajamielikuvan tär keys Big 4 yrityksille heidän houkutellessa nuoria lahjakkuuksia töihin. Tutkimuksessa selvitetään nuorten lahjakkuuksien mahdolliset mielikuva muutokset Big 4 yrityksien työnantajamielikuvasta työllistymisen jälkeen.
Keywords: branding; corporate image; corporate culture; fi=Kansainvälinen liiketoiminta|en=International Business|; Master's Degree Programme in International Business